ADAPTASI TANPA ISI: PENGARUH DESAIN “UNTITLED - I SHOP THEREFORE I AM” KARYA BARBARA KRUGER TERHADAP DESAIN LOGO BRAND SUPREME - Elizabeth Gunawan; Helena Calista; Alfiansyah Zulkarnain (Universitas Trisakti, 2021)
AbstractOne of the conceptual artists of postmodernism, Barbara Kruger, is known for her work that combines visual images with text to convey criticism of social issues directly to society. One of the most famous works that she has is